A Review of Bioinformatics Model and Computational Software of Next Generation Sequencing (International Journal of Innovative Computing, 2019)
In the past decade it has become increasingly the effort for researcher to surpass the bioinformatics challenges foremost in next generation sequencing (NGS). This review paper gives an overview of the computational software and bioinformatics model that has been used for next generation sequencing. In this paper, the description on functionalities, source type and website of the program or software are provided. These computational software and bioinformatics model are differentiating into three types of bioinformatics analysis stages including alignment, variant calling and filtering and annotation. Besides, we discuss the future work and the development for new bioinformatics tool to be advanced.
Keywords: Bioinformatics model; computational software; next generation sequencing